Crossed and uncrossed acoustic reflex growth functions in normal-hearing adults, typically developing children, and children with suspected auditory processing disorder. (September 2015) - Saxena, Udit; Allan, Chris; Allen, Prudence
Abstract Objective: Previous data suggested that children with suspected auditory processing disorders (APD) often show elevated or absent acoustic reflex thresholds, especially in crossed conditions (e.g. Allen & Allan, 2014). This study further explored these effects by measuring acoustic reflex growth functions (ARGF). Design: Crossed and uncrossed ARGF slopes were obtained by linear fits between reflex amplitudes and increases in activator level from threshold to 15 dB above it. Study sample: Normal-hearing adults, typically developing children and children with reported listening difficulties and suspected of having an APD, participated. Results: The ARGF slopes were shallower in crossed than in uncrossed conditions for all groups but the magnitude of the effect was significantly greater in the children with suspected APD. There were no differences between the typically developing children and the adults. Conclusions: The results suggest shallower ARGFs in children with suspected APD. Given the role of the acoustic reflex in facilitating hearing speech in noise these findings may begin to shed light on physiologic explanations for some of the difficulties that are reported by children with suspected APD.